The Antecedents of SMEs’ Customer Loyalty: Examining the role of Service Quality, Satisfaction and Trust - Rajic, Tamara; Nikolic, Ivan; Milosevic, Isidora (Industrija, 2016)
This study aims to propose and empirically examine a model of SMEs’ customer loyalty. The study builds upon previously established relationships among service quality, customer satisfaction and loyalty and enhances previous conceptualizations by incorporating the construct of trust. Hypothesized relationships have been simultaneously examined on a sample of SMEs’ customers, by means of structural equation modelling (SEM) using maximum likelihood as the method of parameter estimation. Results of the study indicate customer satisfaction as the main direct determinant of customer loyalty, followed by trust, whereas the impact of service quality is mediated via satisfaction and trust. Implications of the study have been discussed and directions for future research are highlighted.